Effect of Compression Ratio on Compression Ignition Engine Performance Operating with Biofuel - Akasyah, M Khathri; R., Mamat; Abdul Adam, Abdullah; Gan, Leong Ming; Azri, Alias (2014)
Biofuel becomes more interesting nowadays due to depleting mineral resources of petroleum. Ethanol is one of the biofuel resources derived from an organic substance that is widely used in internal combustion engine. In this study liquid ethanol has been used to study the effect of different compression ratio on a multi-cylinder diesel engine. A numerical work has conducted within one-dimensional simulation software to study the combustion performance in an ignition compression engine. The effect of different compression ratio on the engine performance is critically addressed at constant engine load and various engine speeds. The fuel injection pressure and fuel injection timing have been kept constant throughout the run. The result shows that the brake thermal efficiency gradually increases with the Increase in compression ratio with a simultaneous decrease in brake specific energy consumption.